Elimination of Escherichia coli in Water Using Cobalt Ferrite Nanoparticles: Laboratory and Pilot Plant Experiments - Gastelo, Elmer (2019)
This paper focuses on the synthesis of cobalt ferrite nanoparticles by the sol–gel method and their photocatalytic activity to eliminate bacteria in aqueous media at two different scales: in a laboratory reactor and a solar pilot plant. Cobalt ferrite nanoparticles were prepared using Co(II) and Fe(II) salts as precursors and cetyltrimethyl ammonium bromide as a surfactant. The obtained nanoparticles were characterized by X-ray diffraction, scanning and transmission electron microscopy. Escherichia coli (E. coli) strain ATCC 22922 was used as model bacteria for contact biocidal analysis carried out by disk diffusion method and photocatalysis under an ultraviolet A (UV-A) lamp for laboratory analysis and solar radiation (radiation below 350 W/m2 in a typical cloudy day) for the pilot plant analysis. The results showed that cobalt ferrite nanoparticles have an average diameter of (36 ± 20) nm and the X-ray diffraction pattern shows a cubic spinel structure. Using the disk diffusion technique, it was obtained inhibition zones of (17 ± 2) mm diameter. Results confirm the photocatalytic elimination of E. coli in water samples with remaining bacteria below 1% of the initial concentration during the experiment time (30 min for laboratory tests and 1.5 h for pilot plant tests).